THE ROLE OF MOTORCYCLE PARKING SERVICES ON JALUR C (ROUTE C) IN SUPPORTING THE ECONOMIC ACTIVITIES OF THE COMMUNITY SURROUNDING PT NIKOMAS GEMILANG - Endah Restu Lestari; Fitri Anita; Wiwit Sugiarti; Ade Fauji (International Journal of Multidisciplinary Research and Literature, 2026)
The presence of large-scale industry significantly stimulates the growth of informal sector enterprises in surrounding communities. This study investigates the role of motorcycle parking businesses along Jalan C in supporting the economic activities of communities around PT Nikomas Gemilang, a large shoe manufacturing company in Kibin District, Serang Regency, Banten Province. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation involving three parking business owners and three PT Nikomas Gemilang employees as supporting informants. The results show that these parking businesses have operated for 7–15 years, with an average monthly net income of IDR 7,713,000, far exceeding the Regional Minimum Wage (UMK) in Serang Regency at IDR 5,178,521. Business activities are closely linked to factory shift schedules. These businesses contribute economically by providing main livelihoods for operators and socially by absorbing local labor. Key challenges include market competition, reliance on factory operations, and limited government support. This study recommends business formalization, proper financial recording, and government support programs to strengthen these informal business sectors.